MENYIKAPI DAMPAK SOSIAL MEDIA DI TENGAH REMAJA, KELUARGA DAN MASYARAKAT DI MASA PANDEMI COVID 19 - Siti Aisyah Nurrizqi Rahmadania; Nurismalastri Nurismalastri; Yuga Pratama; Siti Aesah; Djoko Prasetyo (Jurnal Lokabmas Kreatif : Loyalitas Kreatifitas Abdi Masyarakat Kreatif, 2021)
Social media invites anyone who is interested to participate by giving feedback openly, giving comments, and sharing information in a fast and unlimited time. It is undeniable that social media has a great influence in one's life. Someone who starts small can make it big with social media, or vice versa. For the community, not only adults, but teenagers and children have become an addiction that makes users no day without opening social media. The focus of this community service is the role of the family in responding to the adverse effects of social media in the current covid 19 pandemic era where more time uses gadgets that are very closely related to social media, the focus of community service will be directed at the following two things: providing an understanding of the negative and positive influence of social media for adolescents, and how to respond to social media today to be able to deal with social media abuse wisely. This activity uses a lecture, discussion and training approach that refers to phenomenology. Location of activities at Bojongsari community organization, Depok. The conclusion of this activity is responding to social media interactions with the role of parents in supervising youth activities by limiting the time they use gadgets and paying attention to the age of teenagers to access content according to their age. The negative impacts of using social media on teenagers today are identity theft, cyber bullying, child and adolescent abuse, fraud, pornography, violence against children and adolescents, sexual exploitation, self-harm, panic/anxiety/low selfconfidence/stuttering. Social media, and addiction to social media and online games The positive impact of using social media on adolescents: Strengthening friendship relationships, Increasing income in daily life, Social media plays a role in conveying knowledge, Source of referrals and knowledge, Medium to speak, Awareness about surroundings and motivational, and entertainment media.Keywords : Social Media, Teenagers, Family